Dynamics of the critical surface in high-intensity laser-solid interactions: Modulation of the XUV harmonic spectra - Watts, I; Zepf, M; Clark, E; Tatarakis, M; Krushelnick, K; Dangor, A; Allott, R; Clarke, R; Neely, D; Norreys, P (2002)
The generation of harmonics from the interaction of an intense (I ≥ 1018 W cm-2) laser with a solid surface was discussed. At higher laser intensities, the modulation of the harmonic emission spectrum with a periodicity of two to four harmonics was observed. The results showed that the dynamics of the critical surface can be inferred from the shape of the harmonic spectrum.